1998
DOI: 10.1017/s0950268898001423
|View full text |Cite
|
Sign up to set email alerts
|

Rapid spread of the new clone of Vibrio cholerae O1 biotype El Tor in cholera endemic areas in India

Abstract: Using molecular techniques, we investigated whether the clone of Vibrio cholerae O1 biotype El Tor which appeared in Calcutta, India, in 1994 has spread to other cholera endemic areas in the country. The ribotype of 31 of the 33 strains isolated from different parts of India during 1996 and 1997 was identical to the ribotype displayed by the new clone of V. cholerae O1 which emerged in Calcutta in 1994. Likewise, 12 of the 15 strains examined by pulsed-field gel electrophoresis (PFGE) showed identical profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 16 publications
1
21
0
2
Order By: Relevance
“…However, reports of V. cholerae strains resistant to commonly used antibiotics are appearing with increasing frequency and susceptibility testing is now recommended for monitoring of resistance among toxigenic V. cholerae O1 and O139, the two serotypes which cause cholera (4,20,23,29,54).…”
mentioning
confidence: 99%
“…However, reports of V. cholerae strains resistant to commonly used antibiotics are appearing with increasing frequency and susceptibility testing is now recommended for monitoring of resistance among toxigenic V. cholerae O1 and O139, the two serotypes which cause cholera (4,20,23,29,54).…”
mentioning
confidence: 99%
“…Amongst these strains, antibiotic resistance was limited to Ampicillins. However, the characteristics of the cholera bacteria changed in the strains collected in 1996 and afterwards as reported in India, Vietnam and Thailand (Bag et al, 1998;Dalsgaard et al, 1999;Dalsgaard et al, 2000). The genomic analyses revealed that these strains were introduced with a SXT constin gene that regulates for multidrug resistancy (Iwanaga et al, 2004).…”
Section: Cholera Epidemics In Lao Pdr From 1993 To the Presentmentioning
confidence: 92%
“…The causative vibrios collected by the active surveillance in 1993-1995 were all identified as Vibrio cholerae O1 serotype Ogawa and biotype El Tor at the National Institute of Hygiene and Epidemiology (NIHE) (Nakamura et al 1998), and the strains contributed for further publications (Toma et al, 1997). Amongst these strains, antibiotic resistance was limited to Ampicillins.…”
Section: Cholera Epidemics In Lao Pdr From 1993 To the Presentmentioning
confidence: 99%
“…The frequency of plasmid carriage in clinical strains of V. cholerae O1 was less (2%) compared with clinical non-O1 strains (25%) as reported elsewhere. Most of the clinical strains of V. cholerae O1 isolated from different geographical regions lacked the plasmids (48,49), and when present, the size and functions of plasmids were not uniform. A study reported some of the naturally occurring conjugative and non-conjugative plasmids harboring drug resistance determinants in environmental and clinical isolates of V. cholerae encoding genes inducing various antibiotics resistance.…”
Section: Plasmid Mediated Quinolone Resistancementioning
confidence: 99%